The Influence of Educational Communication on Improving Student Learning Achievement - Andi Nursida; Lukman Ismail; Nurul Iftitah Rahmat; Sucitra (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2025)
This study investigates the impact of educational communication on student learning achievement. The purpose of this study is to examine the relationship between teacher-student communication and student learning outcomes. This study uses a mixed method, combining quantitative and qualitative data collection and analysis. A survey of 125 students and 25 teachers was conducted to collect quantitative data. The results of the study show a significant positive correlation between teacher-student communication and student learning outcomes. Teachers who use a student-centered approach and provide clear instructions tend to have students with higher learning outcomes. This study highlights the importance of effective teacher-student communication in improving student learning outcomes, as well as contributing to the existing literature on educational communication and learning outcomes. Keywords : Education; Educational Communication; Learning Achievement; Students